Effects of artificial defects on the mechanical properties of additively manufactured gyroid unit cell - M.A. Wares; M.A. Kader; M.A. Islam; S. Ahmed (Materials & Design, 2025)
Additive manufacturing has enabled the fabrication of complex geometries; however, the fabricated parts often contain a significant number of defects. In this study, we have introduced various types of artificial defects in the gyroid structure and explored their impact on the mechanical responses using finite element (FE) simulations. Three different pore shapes: spherical, ellipsoidal, and cubic are incorporated as defects at varying porosity levels to investigate their influence on collapse mechanisms and elastic properties. The FE model has been validated through the results obtained from quasi-static compression tests on defect-free and defective gyroids manufactured using fused deposition modeling. The results indicate that increasing porosity significantly reduces yield strength and elastic stiffness regardless of pore shape. However, the extent of stress inhomogeneity and plastic strain localization varies with pore shape, which leads to the variation of mechanical properties even at the same porosity levels. Gyroid structure with cubic porosity exhibits maximum stress inhomogeneity and plastic strain localization, resulting in the maximum reduction in yield strength and stiffness, followed by gyroid structure with ellipsoidal and spherical porosity. These findings provide insights into defect severity based on pore shape, enabling the improvement of additive manufacturing processes toward defect mitigation and enhanced mechanical performance.